National medical service
1943-10-20 1943 1940s 15 pages -15- The difficulties of part-time employment in a National Medical Service, comprehensive and dependent on reliable medical certification, would be considerable. A whole-time State Medical Service will be much more preferable. There is no evidence that whole time employment by a L.A. or National Government e.g. Ministry of Health Officers, Medical Officers in Tuberculosis, Infectious diseases, or Maternity Services or in hospitals of L.A. is distasteful to the profession. There is no reason why a good General Practitioner Medical Service should not be made attractive to the profession by good conditions of service. Industrial Medical Service This is of especial interest to the T.U. Movement. At present except in those officers employed by Government Departments the Industrial Medical Officers doing the work, either as C.F.S., or Medical Referees or Factory Medical Officers are private practitioners. The C.F.S. and Medical Referees though appointed by the Home Office are limited by the conditions of their private practice. The Factory Medical Officers in private Industrial establishments, whether employed part time or full time are appointed by the Management of the private firms. Changes are desirable in this service and it is a moot point whether this should not be a State Medical Service, or the appointments made by an impartial Industrial Medical Appointments Board. An extensive development of this service not only for large industrial firms but for small firms and workshops (by combination to employ one full-time Industrial Medical Officer) is greatly needed, not only to secure day-to-day adherence to the minimum statutory requirements of the Factory Act but to protect workers' health in many different ways, especially in dangerous and risky employments. The present Government's policy The main announcements of Government Medical Policy were made during the Parliamentary discussions on the Beveridge Report and by the Minister of Health in the House of Commons on the 9th October, 1941. Very little indication of a definite Medical Services Policy was provided, except that (1) the voluntary hospitals were to be allowed to continue as voluntary institutions and (2) that they would receive Government grants, especially so if medical teaching schools were attached, (3) that hospital patients would be expected to make "a reasonable payment towards the cost of treatment, whether by contributory schemes or otherwise." "Otherwise" may be interpreted to mean by a grant from the Beveridge Social Security Fund but on balance it looks as if the Government intended hospital patients to pay something for that form of treatment. This might entail, as at present, great hardship to individual patients and would necessitate a hospital means test and a continuance of the Almoner System. The pending White Paper setting out the Government's Policy on the proposed comprehensive National Medical Service may provide further elucidation of its intentions. HBM/EM/9.10.43. 292/847/2/113